A Point, A Process, A Meaning : A Psycho-Semiotic Inquiry into the Sorcerer's 3rd Point of Reference and Numeric Indices in Carlos Castaneda's "The Power of Silence" (1987) - Solimeis, Helmi (2024)
This thesis reinterprets Carlos Castaneda’s Teachings of don Juan saga (focusing on vol. 8). Castaneda is considered as both at once; the infamous academic hoaxer and a “sham-man bearing gifts.” From this point of view, readers are invited to engage in a game of uncovering meaning and distinguishing truth from deception. The powers of silence and storytelling are explored within a triangular, theoretical tableau: The study brings together three influential figures – this Godfather of the New Age movement, a post-structuralist semiotician, and a dissident narratologist. The “countercultural Zeitgeist” of the (post-)1960’s West unites post-structuralism and New Age thought. They create intersections with themes of revolt, psychoanalysis, consciousness studies, modern myths, shifting cultural semiotics, and poetic logic. The tableau hinges on analogous tensions between terms drawn from the writings of Castaneda, Julia Kristeva, and Roland Barthes: the Sorcerer’s 3rd point of reference, Kristeva’s 3rd process of the unconscious, and Barthes’s 3rd meaning. These categories undergo psycho-semiotic analysis within a parallelizing post-structural framework, resisting fixed interpretations and pre-assigned reader positions. The focus of this inquiry lies on the narrative process, aiming to unveil the unspoken and the naturalised hidden behind “the veil of the narrative”. This stance is not merely theoretical; it serves as a practical analytical tool. It is described through the interplay of abjection and abreaction, and the secondary analogy of a split (perception, subject, text). When combined with the “sorcery stories,” numeric indices, and “guiding metaphors” from The Power of Silence (1987), these split thirds map out different levels of signification within the narrative web. They can be “keyed open” to reveal an obtuse layer of meaning, intricately woven together by a web of iterative numbers. Additionally, a numerologico–narratological interpretation experiment related to the metaphorical dimension of numbers is provided —an anachronic “key” to the implied narrative “game” or “puzzle” within the macro-structure of the Teachings.